THE ROLE OF CONSTITUTIONAL COURT IN UPHOLDING INDEPENDENCE OF THE CORRUPTION ERADICATION COMMISSION THROUGH DECISION NUMBER 59/-PUU-XVII/2019 - Rayha Rici Saifudin (Program Studi Hukum Tata Negara Islam, Fakultas Syariah, Universitas Islam Negeri (UIN) Datokarama Palu, 2025)
This study investigated important role of the Constitutional Court in upholding the independence of the Corruption Eradication Commission through Decision Number 59/PUU-XVII/2019. This decision marked a historic moment in the eradication of corruption in Indonesia because it successfully annulled several provisions in Law Number 19 of 2019 concerning the second amendment to Law Number 30 of 2002 concerning the Corruption Eradication Commission, which were considered to weaken the authority and independence of the anti-corruption agency. This study is a normative legal research with a statutory and case-based approach. The results show that the Constitutional Court plays a role as a guardian of the constitution, protecting constitutional principles in the eradication of corruption. This decision has a significant impact in strengthening the independence of the Corruption Eradication Commission, particularly regarding the authority to wiretap, investigate, and internal oversight mechanisms. This research also enriches understanding of the role of the Constitutional Court in maintaining the balance of power and protecting independent state institutions. Abstrak Penelitian ini menganalisis peran penting Mahkamah Konstitusi dalam menjaga independensi Komisi Pemberantasan Korupsi melalui Putusan Nomor 59/PUU-XVII/2019. Putusan tersebut menjadi momen bersejarah dalam pemberantasan korupsi di Indonesia karena berhasil membatalkan beberapa ketentuan dalam Undang-Undang Nomor 19 Tahun 2019 tentang perubahan kedua atas Undang-Undang Nomor 30 Tahun 2002 tentang Komisi Pemberantasan Tindak Pidana Korupsi yang dianggap melemahkan kewenangan dan independensi lembaga antirasuah. Penelitian ini merupakan penelitian hukum normatif dengan pendekatan perundang-undangan dan kasus. Hasil penelitian menunjukkan bahwa Mahkamah Konstitusi berperan sebagai penjaga konstitusi yang melindungi prinsip-prinsip konstitusional dalam pemberantasan korupsi. Putusan ini memberikan dampak signifikan dalam menguatkan kembali independensi Komisi Pemberantasan Korupsi, khususnya terkait kewenangan penyadapan, penyidikan, serta mekanisme pengawasan internal. Penelitian ini turut memperkaya pemahaman mengenai peran lembaga Mahkamah Konstitusi dalam menjaga keseimbangan kekuasaan dan perlindungan terhadap lembaga negara yang independen.